2006
DOI: 10.1186/1465-9921-7-122
|View full text |Cite
|
Sign up to set email alerts
|

Altered intercellular communication in lung fibroblast cultures from patients with idiopathic pulmonary fibrosis

Abstract: Rationale: Gap junctions are membrane channels formed by an array of connexins which links adjacent cells realizing an electro-metabolic synapse. Connexin-mediated communication is crucial in the regulation of cell growth, differentiation, and development. The activation and proliferation of phenotypically altered fibroblasts are central events in the pathogenesis of idiopathic pulmonary fibrosis. We sought to evaluate the role of connexin-43, the most abundant gap-junction subunit in the human lung, in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…We have shown that in primary lung fibroblasts from IPF patients there is a reduced expression of Cx43 and, by means of a dye-loading technique, we assessed gap junctional activity and showed a reduced intercellular communication in fibrotic fibroblasts compared with normal cells. The reduced cell-to-cell communication described in IPF fibroblasts is very similar to what has been described in cancer cells and may explain both the release from the restraint of contact-inhibition and uncontrolled proliferation that is present in these diseases [37]. The role of myofibroblasts in IPF and cancer Abnormal wound healing and exaggerated myofibroblast activation are not specific features of IPF; other conditions including fibromatosis, inflammatory myofibroblastic tumours and myofibroblastic cancers, such as myofibromas and myofibroblastomas, are also characterised by uncontrolled proliferation of myofibroblasts [38].…”
Section: Epigenetic and Genetic Abnormalities In Ipf And Cancersupporting
confidence: 54%
“…We have shown that in primary lung fibroblasts from IPF patients there is a reduced expression of Cx43 and, by means of a dye-loading technique, we assessed gap junctional activity and showed a reduced intercellular communication in fibrotic fibroblasts compared with normal cells. The reduced cell-to-cell communication described in IPF fibroblasts is very similar to what has been described in cancer cells and may explain both the release from the restraint of contact-inhibition and uncontrolled proliferation that is present in these diseases [37]. The role of myofibroblasts in IPF and cancer Abnormal wound healing and exaggerated myofibroblast activation are not specific features of IPF; other conditions including fibromatosis, inflammatory myofibroblastic tumours and myofibroblastic cancers, such as myofibromas and myofibroblastomas, are also characterised by uncontrolled proliferation of myofibroblasts [38].…”
Section: Epigenetic and Genetic Abnormalities In Ipf And Cancersupporting
confidence: 54%
“…We have shown that in primary lung fibroblasts from IPF patients there is also a reduced expression of Cx43 that resulted in a reduced gap junctional intercellular communication in fibrotic fibroblasts compared to normal cells. The reduced cell-cell communication described in IPF fibroblasts is very similar to that which has been described in cancer cells and may give an explanation for the release from the restraint of contact inhibition and uncontrolled proliferation that is present in both these diseases [40]. …”
supporting
confidence: 57%
“…Furthermore, in fibroblasts from keloid and hypertrophic scar tissue, compared with normal skin, CX43 levels are significantly lower. We have also shown that in primary lung fibroblasts from IPF patients there is a reduced expression of CX43 which functionally translates into a reduced gap junction intercellular communication (GJIC), an event linked with loss of contact inhibition restraints and as such with uncontrolled proliferation [45].…”
Section: Altered Cell-cell Communicationsmentioning
confidence: 96%